2016
DOI: 10.1093/jac/dkw340
|View full text |Cite
|
Sign up to set email alerts
|

Identification of inhibitors for single-stranded DNA-binding proteins in eubacteria

Abstract: Objectives: The increasing threat of drug-resistant bacteria establishes a continuing need for the development of new strategies to fight infection. We examine the inhibition of the essential single-stranded DNA-binding proteins (SSBs) SSBA and SSBB as a potential antimicrobial therapy due to their importance in DNA replication, activating the SOS response and promoting competence-based mechanisms of resistance by incorporating new DNA.Methods: Purified recombinant SSBs from Gram-positive (Staphylococcus aureu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Some compounds are known to inhibit ssDNA-binding activity of SaSsbA [ 40 ]. For example, ssDNA-binding ability of SaSsbA can be completely suppressed by the presence of 100 μM 9-methyl-2,3,7-trihydroxy-6-fluorone (NSC5426) [ 40 ], a tricyclic planar compound (Figure 13A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some compounds are known to inhibit ssDNA-binding activity of SaSsbA [ 40 ]. For example, ssDNA-binding ability of SaSsbA can be completely suppressed by the presence of 100 μM 9-methyl-2,3,7-trihydroxy-6-fluorone (NSC5426) [ 40 ], a tricyclic planar compound (Figure 13A ).…”
Section: Resultsmentioning
confidence: 99%
“…Some compounds are known to inhibit ssDNA-binding activity of SaSsbA [ 40 ]. For example, ssDNA-binding ability of SaSsbA can be completely suppressed by the presence of 100 μM 9-methyl-2,3,7-trihydroxy-6-fluorone (NSC5426) [ 40 ], a tricyclic planar compound (Figure 13A ). The amino acid sequence of SaSsbC shares 36% identity with that of SaSsbA (Figure 1 ), particularly within the first 110 aa, which is the ssDNA-binding domain, and the model structure of SaSsbC resembles the crystal structure of SaSsbA possessing OB-folds (Figure 10 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent high-throughput screens have been successful in identifying small-molecule inhibitors of SSB-protein interactions (Lu et al, 2010 ; Marceau et al, 2013 ; Glanzer et al, 2016 ). These include an attempt to identify inhibitors of SSB that might disrupt both DNA replication and SOS-mediated resistance pathways within Gram-positive and Gram-negative bacteria (Glanzer et al, 2016 ): following in vitro screening, six molecules were identified which successfully inhibited a broad range of bacterial SSBs, with a further four exhibiting species-specific activity—thereby establishing the potential for both broad-spectrum and species-targeted use. Notably, five of the six compounds were found to have whole-cell activity against a variety of the tested species, of which a single compound, 9-hydroxyphenylfluoron, was associated with minimal activity against the human SSB homolog.…”
Section: The Mycobacterial Dna Replication Machinerymentioning
confidence: 99%
“…13 Some SSB inhibitors as broad-spectrum antibacterial agents targeting S. aureus and other pathogens have been discovered. 12,14 SsbA is referred to as a counterpart of EcSSB. SsbA and SsbB are essential for genome maintenance and transformational recombination, respectively.…”
mentioning
confidence: 99%